Intraurethral Erbium:YAG laser for the management of urinary symptoms of genitourinary syndrome of menopause: A pilot study. Issue 8 (18th April 2018) - Gaspar, Adrian; Maestri, Sandra; Silva, Joaquin; Brandi, Hugo; Luque, Daniel; Koron, Neža; Vižintin, Zdenko
Abstract : Objectives: Genitourinary syndrome of menopause (GSM) combines the conditions of vulvovaginal atrophy (VVA) and urinary tract dysfunction, which is a result of urethral atrophy. There are several treatment methods available for the management of vulvovaginal symptoms of GSM, whereas urinary tract dysfunction often remains overlooked and undertreated. The objective of this pilot study was to assess the safety and efficacy of intraurethral Er:YAG laser treatment of urinary symptoms of GSM. Patients and Methods: Patients with diagnosed GSM, having less than 5% of vaginal superficial cells in the cytology, vaginal pH higher than 5, with urinary symptoms of GSM (dysuria, frequency, urgency) and impaired continence due to urethral atrophy, received two sessions of intraurethral Er:YAG laser with a 3‐week interval in‐between the sessions. Laser energy was delivered in non‐ablative way using Erbium SMOOTH™ mode technology and a 4‐mm thick cannula. Therapeutic efficacy was determined using ICIQ‐SF, the 1‐hour pad test and VAS scores. Occurrence of adverse effects was followed at every visit. Follow ups (FU) were at 3 and 6 months. Results: 29 female patients fulfilling the inclusion criteria were included in this pilot study and received two sessions of the intraurethral non‐ablative Erbium SMOOTH™ laser therapy. Significant improvement was observed in all measured parameters at both FU. ICIQ‐SF improved by an average of 64% at 3 months FU and by 40% at 6 months. The 1‐hour pad test showed a reduction of the quantity of leaked urine by 59% at 3 months FU and by 42% at 6 months FU. All urinary symptoms of GSM improved. Dysuria dropped to 13% and 31% of baseline values at three and 6 months respectively, urinary urgency dropped to 23% and 47% and frequency dropped to 22% and 43% after 3 and 6 months, respectively. Adverse effects were mild and transient. Conclusions: Our findings suggest that intraurethral Er:YAG laser is an efficacious and safe modality for treatment of urinary symptoms of GSM, however, prospective, randomized, and controlled trials with larger number of patients are needed to better assess the long‐term effect of this novel procedure. Lasers Surg. Med. 50:802–807, 2018. © 2018 The Authors. Lasers in Surgery and Medicine Published by Wiley Periodicals, Inc.